PEMBERDAYAAN MASYARAKAT TANJUNG GUSTA MELALUI PERTANIAN HIDROPONIK UNTUK KEBUTUHAN SAYUR SAAT PANDEMI COVID 19 - Baharuddin Baharuddin; Hesti Fibriasari; Bakti Dwi Waluyo; Sapitri Januariyansah (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2021)
Abstract The demand for vegetables by the people of Tanjung Gusta Village, which has increased obstacles due to the Covid 19 pandemic. On the other hand, independent agriculture is difficult to do because land is not available in a densely populated environment. The purpose of this activity is to empower the community to do independent agriculture in their yards through hydroponic technology. The method of activity was carried out by observation, discussion, demonstration, and field practice which was carried out in three stages, namely (1) planning stage; (2) implementation stage; and (3) evaluation stage. The results of the activity can be said to be effective because the activity has been running according to the objectives of the activity. Partners have acquired real knowledge and skills about hydroponic farming in the home page. Hydroponic farming can be an alternative solution to fulfill vegetable needs that can be done in a narrow area such as a home page. Keywords:Vegetables; Hydroponics, Covid 19